Sustainable Business Practices and Dynamic Capabilities as Drivers of Employer Branding and Talent Acquisition & Retention Among Gen Z in Indonesia - Nursakti Niko Rosandy; Ratri Wahyuningtyas (International Journal of Organizational Behavior and Policy, 2026)
The race to get high-quality workers or human resources is becoming increasingly difficult and competitive because Gen-Z is dominating the job market more and more. They focus more on considering a company's commitment to the sustainability of the planet adaptability skills, and the office reputation rather than just the salary. So, the author will examine the relationship between SBP, DCS, EBG, and TAR in the context of Gen Z in Indonesia using quantitative methods, with a total of 680 respondents taken from the tsurvey.id site. The data was analyzed using PLS-SEM to see the relationships between variables. The results show that both sustainable business practices and dynamic capabilities positively contribute to employer branding, although the effect of dynamic capabilities is actually bigger. Employer branding has become the key factor in boosting a company's ability to attract and retain talent. Sustainable business practices don't have a direct impact on talent acquisition and retention if they're not backed by a strong employer image. But dynamic capabilities do influence talent outcomes, both directly and indirectly. In other words, an organization's success in attracting and keeping Gen Z depends on the integration of sustainability practices, the organization's adaptive skills, and credible employer branding.